2020
DOI: 10.3389/fcell.2020.00380
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Resistance Training Modulates Calcaneal Tendon Proteome in the Offspring Exposed to High-Fat Diet

Abstract: The increase in high-energy dietary intakes is a well-known risk factor for many diseases, and can also negatively impact the tendon. Ancestral lifestyle can mitigate the metabolic harmful effects of offspring exposed to high-fat diet (HF). However, the influence of paternal exercise on molecular pathways associated to offspring tendon remodeling remains to be determined. We investigated the effects of 8 weeks of paternal resistance training (RT) on offspring tendon proteome exposed to standard diet or HF diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…More recently, two studies on paternal resistance exercise showed overlapping proteins in the left ventricle and tendon, which change in the same direction (up-regulation), and were present in trained fathers and offspring. 20,24 Other studies revealed that paternal exercise induced modifications in global DNA methylation status, 50 ncRNAs profile, 22,25,51 and protein expression in the hippocampus, 52 skeletal muscle, 21 tendon, 24 heart 20 and liver 53 in the F1 generation (Figure 2).…”
Section: Paternal Exercise On Intergenerational or Transgenerationamentioning
confidence: 98%
See 4 more Smart Citations
“…More recently, two studies on paternal resistance exercise showed overlapping proteins in the left ventricle and tendon, which change in the same direction (up-regulation), and were present in trained fathers and offspring. 20,24 Other studies revealed that paternal exercise induced modifications in global DNA methylation status, 50 ncRNAs profile, 22,25,51 and protein expression in the hippocampus, 52 skeletal muscle, 21 tendon, 24 heart 20 and liver 53 in the F1 generation (Figure 2).…”
Section: Paternal Exercise On Intergenerational or Transgenerationamentioning
confidence: 98%
“…Exercise sessions consisted of 8 ladder climbs with two sets of each load of 50, 75, 90 and 100% of their maximal carrying capacity interspersed by 120 s intervals between each set. 20,24 An additional 30-g load was added to maximal carrying capacity every week according to the overload principle. This protocol induced protective effects on the left ventricle and tendon proteome of offspring exposed to a high-fat diet due to the increase in proteins involved in pathways essential for tissue integrity maintenance.…”
Section: Resistance Training (Rt)mentioning
confidence: 99%
See 3 more Smart Citations